Empowering farmer groups in Yogyakarta, Indonesia, through a participatory development communication model - Muhammad Nur Jaya; Sarwititi Sarwoprasodjo (Jurnal Studi Komunikasi, 2024)
The Participatory development communication model is a form of communication process among farming actors to achieve empowerment. In the era of openness and democratisation, participatory communication is an appropriate approach to encourage farmer groups to be fully empowered. With that, the objective of this research are as follows: formulate and develop participatory development communication models and strategy for empowerment. This study uses a positivistic paradigm with a survey method. The objects of farmer groups are scattered in various places and their characteristics are heterogeneous and widespread, making it suitable for a positivistic approach. The results of the study are: (a) Implementation of participatory development communication model for empowerment and influenced by the characteristics of farmer groups, the quality of information, the role of development agents, environmental support and the use of social capital; (b) strategy for increasing the implementation of participatory development communication: the quality of the characteristics of farmer groups, information, development agents, environmental support and social capital.